Hubungan Depresi dengan Kualitas Hidup Pasien Diabetes Mellitus Tipe 2 - Dewi Ulfani; Safruddin; Sudarman (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Diabetes mellitus is a serious problem for global health regardless of socio-economic status or national boundaries. Diabetes mellitus is a chronic disease that cannot be completely cured and greatly affects the patient's quality of life. The incidence of DM continues to increase both in the world and in Indonesia, so far more research has been about the problem of DM clinics so that more research is needed on the quality of life. In addition, low quality of life and psychological problems can exacerbate metabolic disorders, either directly through a stress harmonic reaction or indirectly through complications. The purpose of this study was to determine the relationship between depression and quality of life of type 2 diabetes mellitus sufferers at the West Kabaena Health Center, Bombana Regency. This type of research is quantitative, with a cross sectional study design. The sample determination is done by using purposive sampling technique with a sample size of 35 respondents. The relationship test was performed using the Continuity Correction test with a significance level of Î± <0.05. The results showed that there was a relationship between depression and the quality of life of type 2 DM patients (p = 0.001 <0.05). The conclusion of the study is that the higher the level of individual depression, the less individual perceptions of the quality of life of type 2 DM patients. From this conclusion it is hoped that nurses will carry out health education and overcome depression in DM sufferers to improve the quality of life.